Efeito inibitório in vitro de ciprofloxacina isolada e em combinação com antifúngicos frente a Coccidioides posadasii e Histoplasma capsulatum var. capsulatum - Caetano, Érica Pacheco (2010)
Coccidioidomycosis and histoplasmosis are systemic mycoses that occur in humans and other animals and are caused by the dimorphic fungi Coccidioides posadasii and Histoplasma capsulatum var. capsulatum, respectively. They are considered important deep mycoses that can lead to several secondary complications. In the past years, the improvement of the techniques applied in mycological diagnosis and the increase in the occurrence of immunocompromising diseases have caused a great impact in the incidence of deep and opportunistic mycoses in the world. In spite of the existence of effective antifungal therapy against coccidioidomycosis and histoplasmosis, the pursue of new drugs to treat theses diseases is necessary. Ciprofloxacin is a classic antibacterial drug that belongs to the group of fluoroquinolones, which inhibit the catalytic activity of DNA gyrase and topoisomerase IV, which are essential in bacterial DNA replication and transcription. Some studies have shown that ciprofloxacin can act on fungal DNA gyrase. Thus, the present study aimed at evaluating the in vitro inhibitory effect of ciprofloxacin (CIP), when associated with amphotericin B (AMB), itraconazole (ITC), voriconazole (VRC) or caspofungina (CAS), on C. posadasii and H. capsulatum var. capsulatum. Sixteen strains of C. posadasii in the filamentous phase and 16 and 9 strains of H. capsulatum in the filamentous and yeast-like phase, respectively, were used. Broth macrodilution and microdilution assays were performed, as described in the documents M38-A and M27-A2, respectively, of the Clinical Laboratory Standards Institute (CLSI). Drug interaction was analyzed by calculating the fractional inhibitory concentration index (FICI), which is defined as the sum of the ratios between the minimal inhibitory concentration (MIC) of each combined drug and the MIC of the same drug isolatedly. Values of FICI smaller or equal to 0.5 indicate the occurrence of synergy. Concerning the isolates of C. posadasii, synergistic interactions were observed for all combinations, especially for the associations of CIP (3.125≤CIM≤12.5 ug mL-1) with ITC (0.0078≤CIM≤0.125 ug mL-1) (n=13/16), CIP (3.125≤CIM≤12.5 ug mL-1) with VRC (0.0078≤CIM≤0.0312 ug mL-1) (n=13/16) and CIP (3.125≤CIM≤12.5 ug mL-1) with CAS (2≤CIM≤8 ug mL-1) (n=14/16). For the isolates of H. capsulatum in the filamentous phase synergistic interactions were also observed for all combinations, with emphasis to the associations of CIP (3.906≤CIM≤62.5 ug mL-1) with ITC (0.00006≤CIM≤0.0078 ug mL-1) (n=14/16) and CIP (31.25≤CIM≤125 ug mL-1) with VRC (0.0156≤CIM≤0.125 ug mL-1) (n=16/16). For H. capsulatum in yeast-like phase, few synergistic interactions were observed for the tested drug combinations. None of the tested combinations presented antagonism. The obtained data may point at a new alternative for the treatment of coccidioidomycosis and histoplasmosis. Thus, it is necessary to investigate the mechanisms of action of these drug combinations on the fungal cellular metabolism and to perform in vivo experiments to confirm the relevance of these findings.